Implementasi Kurikulum Merdeka dalam Pembelajaran Pendidikan Agama Islam (Pai) pada Anak Berkebutuhan Khusus (Abk) Di Slb Negeri 1 Ngawi - Azizunnisak Hidayati Wahyuna (Syntax Literate, 2023)
This research describes the implementation of the Merdeka Curriculum in Islamic Religious Education Learning for Children with Special Needs (ABK) at SLB Negeri 1 Ngawi in the 2022/2023 academic year, conducted at SLB Negeri 1 Ngawi. The method used is a qualitative method. The research subjects consist of three informants, including the Curriculum Vice Principal, Islamic Religious Education teacher, and parents/guardians of the students. Data collection methods include observation, interviews, and documentation, and the data analysis technique follows an interactive analysis model. Data validation is conducted using triangulation, specifically triangulation of sources. The research findings show that the implementation of the Merdeka Curriculum at SLB Negeri 1 Ngawi is running fairly well. The learning process is adjusted by forming classes based on the developmental stages of the children. The school first assesses the children, allowing them to understand their developmental phase and be placed in their respective classes. The implementation of Islamic Religious Education learning is conducive and innovative as teachers use various media and methods. The children's conditions become the main hindering factor in the application of the Merdeka Curriculum at SLB, but with the Merdeka Curriculum, teachers have flexibility in the assessment process, allowing for better exploration of the children's competencies.